2022
DOI: 10.3389/fpsyg.2022.837710
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Motor-Cognitive Interventions on Selected Gait and Balance Outcomes in Older Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundEfficient performance of most daily activities requires intact and simultaneous execution of motor and cognitive tasks. To mitigate age-related functional decline, various combinations of motor and cognitive training have shown promising results. The aim of this systematic review and meta-analysis of randomized controlled trials (RCTs) was to evaluate the efficacy of different types of motor-cognitive training interventions (e.g., sequential and simultaneous) on selected functional outcomes in health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…Previous studies have shown the effectiveness of cognitivemotor interventions in enhancing multicomponent balance tasks, further supporting the potential of DT training in improving postural stability. 10,22 It is important to note that in the present study, which assessed postural stability in a relatively simple static task, improvements in the center of pressure area and balance speed resulting from DT training might not have been fully captured in healthy older adults. Therefore, further research is needed to comprehensively explore the benefits of DT training in the center of pressure area and balance speed.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have shown the effectiveness of cognitivemotor interventions in enhancing multicomponent balance tasks, further supporting the potential of DT training in improving postural stability. 10,22 It is important to note that in the present study, which assessed postural stability in a relatively simple static task, improvements in the center of pressure area and balance speed resulting from DT training might not have been fully captured in healthy older adults. Therefore, further research is needed to comprehensively explore the benefits of DT training in the center of pressure area and balance speed.…”
Section: Discussionmentioning
confidence: 90%
“…21 However, despite this potential harm, when applying DT stimulation to older individuals in clinical practice, the physiological effects can be different, leading to an improvement in their reaction time within their daily activities. 9,10 In this study, the participants in the experimental group engaged in a variety of DT exercises. The exercises were strategically designed to enhance participants' overall postural stability.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that gait changes may indicate some executive dysfunction [ 71 , 72 ]. On the other hand, gait parameters such as speed, cadence and step width can benefit from properly structured interventions [ 73 , 74 ]. Moreover, depending on the type of physical training [ 75 , 76 ], it is possible to simultaneously improve gait and balance and promote neural plasticity [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature also highlights that falls are more prevalent among women [ 52 , 54 ]. Although review and meta-analysis studies have highlighted the benefits of the DT methodology as a useful strategy to activate brain structures [ 42 , 55 ] and concomitantly GP and BB [ 56 , 57 ], as well as LEMS [ 44 ], there are still gaps, in addition to the fact that definitive conclusions were limited by the lack of studies that have investigated the reciprocal effects between all the variables [ 58 , 59 ]. Thus, to date, no studies have specifically examined the effects of physical–cognitive DT training on GP, BB, LEMS, and cognitive vulnerability in a population of cognitively normal older adult women.…”
Section: Introductionmentioning
confidence: 99%